2006
DOI: 10.1128/aem.01528-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Twin-Arginine Translocation Pathway in Corynebacterium glutamicum ATCC 13869

Abstract: Compared to those of other gram-positive bacteria, the genetic structure of the Corynebacterium glutamicum Tat system is unique in that it contains the tatE gene in addition to tatA, tatB, and tatC. The tatE homologue has been detected only in the genomes of gram-negative enterobacteria. To assess the function of the C. glutamicum Tat pathway, we cloned the tatA, tatB, tatC, and tatE genes from C. glutamicum ATCC 13869 and constructed mutants carrying deletions of each tat gene or of both the tatA and tatE gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 58 publications
2
28
1
Order By: Relevance
“…Furthermore, the Tat-pathway-dependent secretion of GFP has been shown to be far superior in C. glutamicum compared with two other Gram-positive bacteria, Bacillus subtilis and Staphylococcus carnosus (Meissner et al, 2007). More recently, there was report of secretion of Streptococcus bovis α-amylase using cspB promoter and signal sequence by C. glutamicum for the efficient utilization of raw starch, identifying C. glutamicum as a very useful host for the expression of heterologous proteins (Kikuchi et al, 2006;Tateno and Akihiko, 2007;Kikuchi et al, 2007).…”
Section: Secretion By C Glutamicum Of Heterologous Proteinsmentioning
confidence: 99%
“…Furthermore, the Tat-pathway-dependent secretion of GFP has been shown to be far superior in C. glutamicum compared with two other Gram-positive bacteria, Bacillus subtilis and Staphylococcus carnosus (Meissner et al, 2007). More recently, there was report of secretion of Streptococcus bovis α-amylase using cspB promoter and signal sequence by C. glutamicum for the efficient utilization of raw starch, identifying C. glutamicum as a very useful host for the expression of heterologous proteins (Kikuchi et al, 2006;Tateno and Akihiko, 2007;Kikuchi et al, 2007).…”
Section: Secretion By C Glutamicum Of Heterologous Proteinsmentioning
confidence: 99%
“…13) The signal peptide sequence of the C. ammoniagenes CspA was used functionally to achieve heterologous protein secretion by C. glutamicum. 14,15) Recently, five or six proteins with sequence similarity to the N-terminal domain of the CspA have been found in the C. glutamicum ATCC13032 genome. 16,17) CspB was found to form the surface (S)-layer that surrounds the cell.…”
mentioning
confidence: 99%
“…Recently, we demonstrated that TG and human epidermal growth factor can be efficiently secreted in active forms by the C. glutamicum Sec pathway (5,6,7,19). In addition, the Tat pathway in C. glutamicum was shown to specifically mediate the secretion of Arthrobacter globiformis isomaltodextranase (IMD) (14), as well as green fluorescent protein (GFP) (30) carrying an E. coli TorA signal peptide (20,37). We also showed that pro-TG and pro-PG could be produced using the Tat pathway in C. glutamicum (20,21).…”
mentioning
confidence: 99%
“…In addition, the Tat pathway in C. glutamicum was shown to specifically mediate the secretion of Arthrobacter globiformis isomaltodextranase (IMD) (14), as well as green fluorescent protein (GFP) (30) carrying an E. coli TorA signal peptide (20,37). We also showed that pro-TG and pro-PG could be produced using the Tat pathway in C. glutamicum (20,21). More recently, Tat pathway-dependent secretion of GFP has been shown to be far more efficient in C. glutamicum than in two other gram-positive bacteria, B. subtilis and Staphylococcus carnosus (28), indicating that C. glutamicum could be a useful host for the production of heterologous proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation